PENGARUH KADAR FLY ASH TERHADAP KEBUTUHAN AIR DAN KUAT TEKAN HIGH VOLUME FLY ASH - SELF COMPACTING CONCRETE (HVFA - SCC) - Fitria Ekasanti, Aisyiyah; A Kristiawan, Stefanus; Sunarmasto, Sunarmasto (Program Studi Teknik Sipil FT UNS, 2014)
The conventional concrete casting for a solid reinforcement using vibrator tool has not ensured the achievement of optimal compactness. In order to achieve the maximum compactness, a fresh concrete should be produced high-flowable and self-compactable. The use of fly ash with soft round particle grains caused a very small friction between the grains, therefore it can increase the flowability of concrete mix. It can reduce the water volume in concrete mix, it makes the concrete potency produced will have a high compressive strength as the structural concrete application demand. The purpose of this research is to analyze the effect of fly ash content at respected water demand on fresh properties and compressive strength of HVFA-SCC. The method employed in this research was the experimental one, by means of developing concrete mix composition using fly ash to subtitute a fraction of cement at minimum water content to produce HVFA-SCC. The fresh concrete were characterited by 5 (five) methods: flow table test, j-ring flow table test, l-box test, box type test and v-funnel test. Testing of hardened concrete was conducted by crushing the cylinder speciments on compression testing machine at the age of 7, 28, 56 and 90 days. The result of research showed that the higher fly ash can decrease the water content, which affects the fresh properties of concrete. In this research, the higher fly ash and lower water content, results in several mix concrete comply with the fresh properties requirement of SCC. The higher fly ash can increase or decrease the value of compressive strength. This research indicated that the use of fly ash to subtitute a fraction of cement can consequently reduce the water, the 132 kg water volume on 70% fly ash HVFA-SCC produced the highest compressive strength (at the age of more than 28 days).